POLICY FOR IMPROVING MENTAL HEALTH THROUGH AN INTEGRATED APPROACH - Umy Yonaevy (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
In the face of the growing global mental health challenges, there is an urgent need to formulate and implement effective and sustainable mental health strategies. The study focuses on mental health and an integrated approach. This integrated approach emphasizes the importance of integrating promotional, preventive, curative, and rehabilitative efforts into a coherent framework to address mental health issues at all levels of society. The research method used is the study of literature by searching for references in accordance with the context of research. The results of the research show that policies to enhance mental health through an integrated approach offer effective strategies in dealing with complex and diverse mental health challenges. By integrating services across the spectrum of preventive, promotional, curative, and rehabilitative in a context that supports cross-sector cooperation, this policy promotes the creation of a more inclusive and inclusive mental health support system. The key to the successful implementation of this policy lies in joint inter-sectoral commitment, in-depth understanding of the local context, and sustainable investment in human and financial resources.